Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1966
DOI: 10.1192/bjp.112.487.603
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of a Group of Patients who have Attended both the Child and Adult Departments of the same Psychiatric Hospital

Abstract: The relationship between child and adult psychiatric illness, though of fundamental importance, has received scant attention, perhaps because of the split which exists between the study and treatment of children and of adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1968
1968
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…Even the identification of groups with multiple risk factors (Tables 7 and 8) did not yield high numbers of cases and attempts to improve on poor sensitivity by lowering thresholds for selection inevitably led to corresponding falls in specificity. These modest relationships between childhood behaviour and temperament and adult neurosis were consistent with previous work using patient samples (Warren, 1965;Pritchard& Graham, 1966;Robins, 1966;Mellsop, 1972;Kupferetal., 1975;Zeitlin, 1986) and population samples (Livson & Peskin, 1967;Block, 1971;Abe, 1972;Kandel & Davies, 1986). Gontinuity was in fact greater than expected from some studies (e.g.…”
Section: Type Of Adult Disorder Indicatedsupporting
confidence: 89%
“…Even the identification of groups with multiple risk factors (Tables 7 and 8) did not yield high numbers of cases and attempts to improve on poor sensitivity by lowering thresholds for selection inevitably led to corresponding falls in specificity. These modest relationships between childhood behaviour and temperament and adult neurosis were consistent with previous work using patient samples (Warren, 1965;Pritchard& Graham, 1966;Robins, 1966;Mellsop, 1972;Kupferetal., 1975;Zeitlin, 1986) and population samples (Livson & Peskin, 1967;Block, 1971;Abe, 1972;Kandel & Davies, 1986). Gontinuity was in fact greater than expected from some studies (e.g.…”
Section: Type Of Adult Disorder Indicatedsupporting
confidence: 89%
“…This can be demonstrated for psychological health potential by research showing that childhood behaviour and personality are associated with adult psychiatric disorder or tendency to psychiatric disorder.56 This is further supported by work linking childhood behaviour and temperament with adult neurosis.57"' Similarly, height has been shown to be an indicator for the risk of future morbidity, as can be demonstrated by the association of short stature with a higher mortality from stroke, ischaemic heart disease, rheumatic heart disease and chronic bronchitis.62 However, the associations between childhood health potential and later excess mortality and morbidity should not be thought of as a direct link. A study of Finnish men aged [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] years,6" found that adult socioeconomic conditions were far more important in determining risk of all cause cardiovascular mortality than childhood conditions. This highlights the importance of conditions throughout life for their contribution to risk of excess morbidity.…”
Section: Controlling For Confounding Variablesmentioning
confidence: 99%
“…It has been found that socially incompetent children are more likely to drop out of school (Ullmann, 1957), become juvenile delinquents (Roff, Sells, and Golden, 1972), underachieve academically, and exhibit high levels of physical and verbal aggression (McCandless, 1967). Similarly, several retrospective studies of adult psychiatric patients (e.g., Pritchard and Graham, 1966;Watt, Stolurow, Lubinsky, and McClelland, 1967) have indicated that those patients diagnosed as schizophrenic, sociopathic, and/or mentally deficient frequently have psychiatric records dating from early childhood.…”
mentioning
confidence: 99%